Influence of Statin Use on Endothelial Function: From Bench to Clinics - Martinez-Gonzalez, Jose; Badimon, Lina (Current Pharmaceutical Design, 2007)
Endothelial dysfunction has been shown to be a prognostic factor for cardiovascular disease and improvement of endothelial dysfunction prevents cardiovascular event presentation. Endothelial dysfunction is associated to a reduced nitric oxide (NO) bioactivity, as a result of the impairment of NO synthesis/release by the endothelial NO synthase (eNOS) or by inactivation of NO. Endothelial dysfunction measurements are valuable surrogate markers to assess the effectiveness of interventions addressed to prevent o treat coronary heart disease (CHD). Dyslipemia and other cardiovascular risk factors promote endothelial dysfunction and life style changes and pharmacological treatment, particularly HMG-CoA reductase inhibitors (statins), have shown early improve of endothelial-dependent vasomotion. Statins efficiently reduce plasma LDL cholesterol, an effect that may account for their beneficial effect on endothelial function, but they also reduce cellular levels of isoprenoid compounds relevant for the bioavailability of NO. Statins restore NO production by several mechanisms, including up-regulation of eNOS mRNA and protein levels and preservation of NO inactivation by reactive oxygen species (ROS). These effects are mediated, at least in a part, through mechanisms independent of their lipid lowering effect (pleiotropic effects). In this article we discuss the relevance of endothelium-dependent effects on the early and delayed clinical benefit of statins, as well as the multiple ways by which statins may restore endothelial function acting not only on the endothelium but also on endothelial progenitor cells (EPC), which likely could contribute to both ischemia-induced neovascularization and endothelial regeneration after injury.
Keywords: statins